Feminism, Anthropology and the Politics of Excision in Mali: Global and Local Debates in a Postcolonial World - Gosselin, Claudie (Anthropologica, 2022)
This article examines the politics and discourses surrounding female circumcision, and explores ethical approaches to its study for feminist anthropologists. First I present an overview of the international debate on these operations, and review the literature on "female genital mutilation." Unfortunately these writings that are meant to help empower African women can "colonize" them (after Mohanty, 1991). Second, the current debates around the practice in Mali are discussed. The issue has become a metonym for politically, ideologically and economically motivated discussions on gender, age, caste, Islam and Westernization.